2015
DOI: 10.1038/onc.2014.467
|View full text |Cite
|
Sign up to set email alerts
|

CACNA2D2 promotes tumorigenesis by stimulating cell proliferation and angiogenesis

Abstract: In the present study, we have assessed whether a putative calcium channel α2δ2 auxiliary subunit (CACNA2D2 gene) could be involved in prostate cancer (PCA) progression. We therefore carried out experiments to determine whether this protein is expressed in PCA LNCaP cells and in PCA tissues, and whether its expression may be altered during cancer development. In addition, we evaluated the influence on cell proliferation of overexpressing or downregulating this subunit. In vitro experiments show that α2δ2 subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
0
47
0
3
Order By: Relevance
“…Several of the genes, such as Mmp8, Dock10, Hoxd3 and Fat3 , have previously been reported to show mutation or altered expression in cancer and particularly metastasis [4145]. Two genes, Cacna2d2 and Dbc1 are candidate tumour suppressors in other cancers [46, 47]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the genes, such as Mmp8, Dock10, Hoxd3 and Fat3 , have previously been reported to show mutation or altered expression in cancer and particularly metastasis [4145]. Two genes, Cacna2d2 and Dbc1 are candidate tumour suppressors in other cancers [46, 47]. …”
Section: Resultsmentioning
confidence: 99%
“…However, in the mouse genome, the orthologs reside on different chromosomes. The importance of this gene in MM in undetermined, though it has been linked to tumorigenesis in prostate cancer [46] and loss of expression has been demonstrated in non-small cell lung cancer [54]. …”
Section: Discussionmentioning
confidence: 99%
“…CACNA2D2 encodes a voltage gated calcium channel, which when mutated in mice leads to the development of an ataxic gait and epilepsy (Barclay et al, 2001). No studies on CACNA2D2 have been performed in AML, however, functional studies have shown both tumour suppressor activity in lung cancer (Carboni et al, 2003) and oncogenic properties in prostate cancer (Warnier et al, 2015). Overall, CACNA2D2 is thought to be a tumour suppressor gene, as it is part of a 120kb region recurrently deleted in a variety of solid tumours (Hesson et al, 2007).…”
Section: Epigenetic Landscape Differ Between T(3;21) and T(8;21) Leukmentioning
confidence: 99%
“…; Warnier et al . ). Moreover, the importance of TRPC6 as a modulator of angiogenic potential has been revealed in glioma cells (Chigurupati et al .…”
Section: Introductionmentioning
confidence: 97%